Pengaruh Kompetensi Aparatur dan Pemanfaatan Teknologi Terhadap Kualitas Laporan Keuangan Desa Di Kecamatan Purwadadi - Vina Putriani Nursalin; R. Budi Hendaris (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to determine the effect of apparatus competence and technology utilization on the quality of village financial reports in Purwadadi District both partially and simultaneously. This type of research is quantitative with a total of 36 respondents with purposive sampling technique. Then the data collection technique uses library research and field research, and the data analysis technique uses descriptive and associative methods. The data analysis technique used is multiple linear regression analysis using IBM SPSS Statistics 27 software. The test results show that partially, the competence of the apparatus does not have a significant effect on the quality of village financial reports in Purwadadi District, while the use of technology has a significant effect on the quality of village financial reports in Purwadadi District. However, when viewed simultaneously, the competence of the apparatus and the use of technology have a significant effect on the quality of Village financial reports in Purwadadi District. the results of this study are expected to provide encouragement to further optimize the use of technology in the preparation of financial reports. In addition, although the competence of the apparatus does not have a significant effect partially, increasing competence is still important in the long term in order to keep up with technological developments and village financial administration systems and also become a reference for similar studies in other regions that have similar characteristics.